Cancer-Related Pain Management and the Optimal Use of Opioids - Reis-Pina, Paulo (2015)
Pain relief is vital to the treatment of cancer. Despite the widespread use and recognition of clinical recommendations for the management of cancer-related pain, avoidable suffering is still prevalent in patients with malignant disease. A gap exists between what is known about pain medical management and actual practices of patients, caregivers, healthcare professionals and institutions. Opioids are the pillar of the medical management of moderate to severe pain. The prescription of opioid analgesics – by a registered medical practitioner for absolute pain control – is a legitimate practice. In this article we look at patients’ fears and physicians’ generalhesitations towards morphine and alike. We examine misconceptions that yield fallacies on the therapeutically use of opioids and, therefore, sustain inadequate pain management.